Multiprocessor scheduling of processes with release times, deadlines, precedence, and exclusion relations - Xu, J. (IEEE transactions on software engineering, 1993)
The author presents a scheduling algorithm that solves the problem of finding a feasible nonpreemptive schedule whenever one exists on M identical processors for a given set of processes such that each process starts executing after its release time and completes its computation before its deadline. A given set of precedence relations and a given set of exclusion relations defined on ordered pairs of process segments are satisfied. This algorithm can be applied to the important problem of automated pre-run-time scheduling of processes with arbitrary precedence and exclusion relations on multiprocessors in hard-real-time systems.< >